Light aircraft and resource monitoring - Gwynne, M.D.; Croze, H. (International Livestock Centre for Africa, 1981)
Discusses the beginnings & developments of light aircraft survey approaches in Eastern Africa and elsewhere for animal census, habitat & ecological data collecting; mentioning techniques being currently developed & applied to situations & zones of the world, and the need for a standardized survey methodology of resource monitoring.